Anza palaeoichnological site. Late Cretaceous. Morocco. Part I. The first African pterosaur trackway (manus only). (October 2017) - Masrour, Moussa; Pascual-Arribas, Carlos; de Ducla, Marc; Hernández-Medrano, Nieves; Pérez-Lorente, Félix
Abstract: Cretaceous pterosaurs tracksites are very rare worldwide. Until now, only one African Cretaceous site withtracks of ( Agadirichnus elegans and Pteraichnus ) was known. This makes the discovery of a new outcrop in the Upper Cretaceous of Anza (Morocco) the third manifestation of this type of footprint in Africa, extending the existence of such traces from the Coniacian-Santonian to the Maastrichtian. The site contains only manus tracks, which can be explained as a result of erosion of pes prints. The lack of pes prints and the morphometric characteristics of the manus prints only allow us to relate these prints to Agadirichnus, Pteraichnus or maybe to a new ichnogenus. It is possible that the trackmakers are related to Ornithocheiroidea or Azhdarchoidea superfamilies whose fossil bones have been found from the Late Cretaceous in Morocco. Highlights: The second reported occurrence of pterosaurs tracksites in the UpperCretaceous of Africa, extending the existence in time of such traces from the Coniacian-Santonian to the Maastrichtian.